Playing at life: The role of play in the prismatic illumination of the self. Issue 2 (1st July 2014) - Wooster, Roger
Playback Theatre has had some success over the past decade in establishing itself as a valid form of therapeutic drama. This article considers its processes and approaches against the background of other twentieth-century developments in drama in education and drama therapies. This article traces the connections between key practitioners from drama in education (including Dorothy Heathcote, who coined the term 'prismatic illumination') and the developing praxis of psychodrama, drama therapy and Playback Theatre. Is Playback Theatre truly for self-discovery by the Teller, or for voyeuristic consumption by an audience accustomed to reality television? There has always been a tension in this area of work (be it in an educational or therapeutic context) between the importance of the process/personal journey and the desirability of an observed outcome. The nature of these tensions are examined by this article, and ethical questions are posed regarding the processes being used.